The effect of physical exercise on apathy in older adults: a systematic review and meta-analysis - Haichang Jia; Zhengyang Mei; Yang Luo; Xintong Mou; Jing Huang (Frontiers in Public Health)
ObjectivesThe objectives of this systematic review and meta-analysis were to evaluate the overall efficacy of physical exercise on apathy in older adults and to provide evidence for alleviating and improving apathy.MethodsThis study was conducted following the PRISMA guidelines and the Cochrane Handbook for the Evaluation of Systems of Intervention. A comprehensive search was performed across databases, including Cochrane, EMBASE, PubMed, and Web of Science, with a cutoff date of January 2025. Data extraction, organization, and quality assessment were performed using appropriate software. Stata was used to analyze and process the data and test for publication bias.ResultsThe analysis included 9 RCTs involving a total of 356 participants. The meta-analysis revealed a significant improvement in apathy (SMD = −0.32; 95% CI −0.53 to −0.11; p < 0.01) after the physical exercise intervention.ConclusionPhysical exercise effectively alleviates and improves apathy in older adults. Physical exercise is characterized by low risk and high therapeutic benefits and can be used as an alternative or adjunct to medications for the treatment of apathy. Given its favorable safety and efficacy profile, physical exercise should be an important intervention in the treatment of apathy in older adults, while control of the intensity of exercise and supervision of the safety of the exercise process must be considered.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251123484, CRD420251123484.